The Role of Case Definitions in Myalgic Encephalomyelitis and Chronic Fatigue Syndrome - Jason, Leonard; Fragale, Samantha (Socialmedicinsk tidskrift, 2016)
Case definitions are essential for any disease, both in terms of reliability identifying those that are diagnosed and those that are not diagnosed. Myalgic Encephalomyelitis and Chronic Fatigue Syndrome. There have been a number of different criteria proposed for Myalgic Encephalomyelitis and Chronic Fatigue Syndrome, and a recent name change has been proposed by the Institute of Medicine (IOM) in 2015. It is critical to develop a consensus on a clinical and research case definition. Two studies have been conducted at DePaul University and they are reviewed in this article.  Significant reliability issues were found for the recent IOM recommendations, and implications of these findings are discussed.